Cell-Mediated Hypersensitivity in Rabbits Infected with Trypanosoma brucei and Trypanosoma rhodesiense - Tizard, I. R. (1971)
Animals infected with strains of Trypanosoma brucei and T. rhodesiense exhibited cutaneous hypersensitivity to intradermal administration of antigen. This reactivity was of two types, an Arthus-type, antibody-mediated reaction which reached maximum intensity 4 hr after injection and a delayed-type, cell-mediated reaction which reached maximum intensity 24 hr after injection. This delayed-type hypersensitivity appeared in rabbits not earlier than 3 weeks after onset of infection. It did not occur in animals which received dead organisms. There was a cross-reaction in both types of reactivity between antigens prepared from T. brucei and T. rhodesiense. The delayed-type hypersensitivity was transferred to normal rabbits by intravenous inoculation of washed living cells from the spleen of a rabbit which showed delayed hypersensitivity. Dead cells failed to transfer hypersensitivity. The histological picture of the indurated area was typical of a delayed-type reaction.